Effect of nitrogen gas-assisted cooling on TIG weld distortion and mechanical properties of AA5083 aluminum alloy - Fuad Dwi Hanggara; Rama Dani Eka Putra; Tessa Zulenia Fitri; Handi Wilujeng Nugroho; Dhanang Suryo Prayogo (Politeknik Negeri Lhokseumawe, 2025)
This study investigates the effect of nitrogen gas-assisted static cooling on weld distortion and mechanical properties of AA5083 aluminum alloy joined by Tungsten Inert Gas (TIG) welding. Although various cooling techniques have been reported to control heat input and distortion in aluminum welding, the combined influence of static nitrogen cooling and welding current on both distortion behavior and local mechanical properties of AA5083 remains insufficiently understood. Three welding current levels (100 A, 110 A, and 120 A) were applied while maintaining constant welding speed, arc voltage, and shielding gas flow. Mechanical properties, including tensile strength and Vickers hardness, were evaluated across the weld metal, Heat-Affected Zone (HAZ), and base metal. Thermal-induced distortion was analyzed using 3D profiling and validated through Analysis of Variance (ANOVA) statistical tests. The results indicate that a welding current of 100 A with static nitrogen cooling minimizes distortion and achieves the highest tensile strength (197.41 MPa). The highest yield strength was recorded at 120 A (160.31 MPa), while the maximum hardness values were observed in the weld metal at 110 A (135.83 VHN), HAZ at 120 A (117.63 VHN), and base metal at 100 A (124.1 VHN). Statistical analysis confirms that welding current significantly influences both distortion and mechanical outcomes (p 0.05), while the cooling method shows a moderate effect. These findings demonstrate that nitrogen-assisted static cooling offers a practical approach to improving weld quality by balancing dimensional stability and mechanical performance in precision aluminum welding applications.